Estimate of Life of Reservoirs Included in the First Phase of Development of Damodar Valley Project - Murthy, B N; Iyengar, N S (Journal of Soil and Water Conservation, 2022)
To estimate the quantity of silt that settles down in the reservoir, the mon- soon inflow into the reservoir is divid- ed into three portions:Portion A — The portion of the inflow which will be stored in the reservoir for release during the dry period. This corres- ponds to storage for seasonal regulation. All silt including bed load in this portion will settle down as it gets plenty of time to do so.Portion B — The portion of the inflow which will be held back temporarily for a day or two during flood control operation. This applies to Maithon and Panchet Hill only. In an average about of the flood reserve is expected to be used in this way about 5 times during the monsoon. A portion of the silt that can settle down during this interval is to be assessed. For this purpose the average depth of water is taken at 50 ft. and the period of fall about 1} days which means that all particles with falling velocity in excess of about 1b ft. per hour will settle. This corresponds to all bed loads, all gravel, all sand, all coarse silt and 75 per cent of fine silt contained in this portion of inflow.Portion C — The remaining portion of the inflow just passes through the reservoir and is released as it comes. During its passage through the reservoir a portion of its charge settles down. This is estimated as shown below :The rate of fall of sediment particles of different sizes are assumed as per attached curve (FIG 1 ) recommended by Hunter Rouse in his book " Engineering Hydraulics". This curve shows that the falling velocity of particles of different sizes are as follows:Fine silt, less than 6 ft. per hour Coarse silt, 6 ft. per hour to 70 ft. per hour Sand, 70 ft. per hour to 1200 ft. per hour Gravel, more than 1200 ft. per hour.